Perceived neighborhood social cohesion and cardiometabolic risk: a gene × environment study. (2nd January 2020) - Robinette, Jennifer W.; Boardman, Jason D.; Crimmins, Eileen
ABSTRACT: People living in socially cohesive neighborhoods generally have better health. We extend this research by evaluating the hypothesis that perceived neighborhood cohesion may influence health by attenuating genetic liability for cardiometabolic risk factors. Using data from the Health and Retirement Study ( n = 6615; mean age 69.7), we conducted a gene × environment interaction study hypothesizing that perceived neighborhood cohesion would attenuate the link between polygenic scores for waist-to-hip ratio (WHR) and body mass index and a measure of multisystem cardiometabolic risk (systolic and diastolic blood pressure, heart rate, A1c, C-reactive protein, and total and high-density lipoprotein cholesterol). In support of the hypothesis, results indicated that among people perceiving low neighborhood cohesion, higher WHR polygenic scores were associated with greater cardiometabolic risk. In contrast, the genetic-cardiometabolic risk link was much attenuated among those living in neighborhoods perceived as socially cohesive. Our results support community-level interventions to enhance the social cohesiveness of individuals' neighborhoods which may provide health benefits by reducing the risks associated with known genetic risk factors.